An appropriate interface design for attract emotions of remedial children by applying ARCS model (attention) / Nurul Assikin Khamis - Khamis, Nurul Assikin (2015)
Emotional is an important part that contributes on the cognitive in learning process among children. The behavior and emotional problem will distract the attention and feeling among others. An appropriate interface design is an interface that designed for special remedial children to assess the presence of the attraction on their emotions using material of learning. A remedial child is a category of slow learner children that has difficulties on 3M skills (Membaca, Mengira and Menulis) and lower cognitive memory. The interface design that was designed based on the elements attention on ARCS Model and review data analysis from interviewees. This research used the observation method on remedial children to see their emotions during learning. This research includes the strength, limitation and the future recommendation toward applying emotions on interface design for material on learning education.